Molecular basis of resistance to leaf spot disease in oil palm - Wibowo, Cahyo S.; Susilo, Ricki; Ernawan, Reza; Apriyanto, Ardha; Alshaharni, Mohammed O.; Smith, Graham R.; Gatehouse, Angharad M. R.; Edwards, Martin G. (Frontiers in Plant Science, 2024)
Leaf spot disease caused by the fungal pathogen Curvularia oryzae is one of the most common diseases found in oil palm (Elaeis guineensis) nurseries in South East Asia, and is most prevalent at the seedling stage. Severe infections result in localized necrotic regions of leaves that rapidly spread within nurseries leading to poor quality seedlings and high economic losses. To understand the molecular mechanisms of this plant-pathogen interaction, RNA-Seq was used to elucidate the transcriptomes of three oil palm genotypes with contrasting pathogen responses (G10 and G12, resistant and G14, susceptible) following infection with C. oryzae spores. Transcriptomes were obtained from Illumina NovaSeq 6000 sequencing of mRNA at four different time points (day 0, before treatment; day 1, 7, and 21 post treatment). Analysis of differentially expressed gene (DEG) profiles in these three genotypes provided an overview of the genes involved in the plant defence. Genes involved in disease resistance, phytohormone biosynthesis, gene regulation (transcription factors), and those encoding proteins associated with cell wall hardening were identified and likely contribute to the resistance of oil palm to C. oryzae. Such genes represent good candidates for targets to enhance oil palm productivity and resilience through molecular breeding approaches.